The Pharmacists' Role in Identifying and Supporting Victims of Human Trafficking. Issue 3 (3rd July 2019) - Palombi, Laura C.; Van Ochten, Hannah; Patz, Caroline
ABSTRACT: Human trafficking (HT), an egregious human rights violation and escalating form of modern-day slavery, has received increasing global attention over the last decade. Despite the fact that the pharmacist is one of the most accessible health-care providers and may have more contact with trafficking victims than other health-care providers in the United States, there is currently little guidance available for pharmacists who wish to support victims of HT. To address this gap, this article provides guidance for pharmacists and pharmacy personnel who wish to provide the best possible care and referral for victims of HT.